An evidence and consensus based guideline for acute diarrhoea management. Issue 2 (1st August 2001) - Armon, K; Stephenson, T; MacFaul, R; Eccleston, P; Werneke, U
Abstract : OBJECTIVE: To develop an evidence and consensus based guideline for the management of the child who presents to hospital with diarrhoea (with or without vomiting), a common problem representing 16% of all paediatric medical attenders at an accident and emergency department. Clinical assessment, investigations (biochemistry and stool culture in particular), admission, and treatment are addressed. The guideline aims to aid junior doctors in recognising children who need admission for observation and treatment and those who may safely go home. EVIDENCE: A systematic review of the literature was performed. Selected articles were appraised, graded, and synthesised qualitatively. Statements on recommendation were generated. CONSENSUS: An anonymous, postal Delphi consensus process was used. A panel of 39 selected medical and nursing staff were asked to grade their agreement with the generated statements. They were sent the papers, appraisals, and literature review. On the second and third rounds they were asked to re-grade their agreement in the light of other panellists' responses. Consensus was predefined as 83% of panellists agreeing with the statement. RECOMMENDATIONS: Clinical signs useful in assessment of level of dehydration were agreed. Admission to a paediatric facility is advised for children who show signs of dehydration. For those with mild to moderate dehydration, estimated deficit is replaced over four hours with oral rehydration solution (glucose based, 200–250 mOsm/l) given "little and often". A nasogastric tube should be used if fluid is refused and normal feeds started following rehydration. Children at high risk of dehydration should be observed to ensure at least maintenance fluid is tolerated. Management of more severe dehydration is detailed. Antidiarrhoeal medication is not indicated. VALIDATION: The guideline has been successfully implemented and evaluated in a paediatric accident and emergency department.